Is Reconstructive Plastic Surgery Appropriately Valued? Comparison of Reimbursement per Unit Time for Reconstructive versus Aesthetic Procedures - Alexa De la Fuente Hagopian, MD; Souha Farhat, MD; Narainsai K. Reddy, MS; Sebastian Guadarrama-Sistos Vazquez, MD; Pablo L. Padilla, MD; Anthony Echo, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The work relative value units (wRVUs) system was established as a quantifier of physician labor, technical skill, medical decision-making, and training time required to complete a surgical procedure; hence, more challenging operations should theoretically result in higher reimbursement or compensation. Our purpose was to highlight the discrepancies between insurance-based reconstructive and fee-for-service aesthetic procedures based upon dollar/unit time. Methods:. We analyzed national data from the American College of Surgeons National Surgical Quality Improvement Program, Aesthetic Surgery Databank, and Centers for Medicare and Medicaid Services to compare reimbursement for 8 reconstructive microsurgery and 3 aesthetic procedures and assessed operative times and reimbursement rates, then calculated “relative value unit per unit time” to measure compensation efficiency. Results:. This difference in remuneration translates to a 4.7× difference, with an overwhelming gap of $25.26 per minute between microsurgical reconstructive and aesthetic cases. These findings suggest that aesthetic cases are more profitable considering the compensation per unit time. Based on national rates of reimbursement, there is a large discrepancy between reimbursement in microsurgical reconstructive procedures and aesthetic procedures. Conclusions:. We demonstrated that complexity and time are not directly related to compensation.